Pemanfaatan Tumbuhan Dapdap dan Canging (Erythrina) dalam Pengobatan Usada - I Nyoman Arsana (The Ethnobiological Society of Indonesia, 2021)
Traditional Balinese medicine is known as usada, and is mentioned in lontar manuscripts. Medical practices of usada use plants as medicinal ingredients. One of the plants utilized is the Genus Erythrina. This research aims to study the use of the Erythrina in the usada. Research using the library method. The unit of analysis is 9 of usada manuscript. Data analyzed qualitatively. The study found three species of Erythrina used in the treatment of usada namely; Erythrina fusca Lour, Erythrina euodiphylla Hassk, and Erythrina subumbrans (Hassk.) Merr. Erythrina fusca is used to treat tiwang, anuria, cough, eye pain, nguwus, sarab angin, rare kena men bajang. Erythrina euodiphylla Hassk is used to treat tiwang, smallpox, defecate with blood and pus, tuju upas, herves, impotence. Erythrina subumbrans (Hassk.) Merr., is used to treat smallpox, hemorrhoids, mokan, tiwang, cough, tuju anglinuh, eye pain, beteg, stomach ache, pamalinan, krambit ring lambe, buh barah, taneng tuh, and sprue. Plants are used in the form of polyherbals, by drinking as loloh, eaten, boreh (scrub), sembar (blurted out), tutuh (drops), tempel (attached to), oles (polish up).